THE INFLUENCE OF DIGITAL MARKETING ON SHARIA MSME INCOME (STUDY OF SHARIA MSMEs IN DELI SERDANG REGENCY) - Muhammad Hafizh; Purnama Ramadani Silalahi (LPPM, 2022)
The use of digital marketing during the pandemic is very helpful for SMEs in developing their business. The purpose of this study was to determine the effect of digital marketing on MSME business actors in Deli Serdang district. The study used quantitative methods with questionnaire data collection distributed using the G-form. The results of this study indicate that digital marketing has a significant effect on the income of Sharia MSMEs in Deli Serdang district. The implication of this research are that with digital marketing, businesses get the opportunity to maintain good relations with customers, expanding market access for their business progress.